Exploring African Student Video Game Play: A Connected Learning Theory Perspective. - Bayeck, Rebecca Yvonne (Journal of Pan African Studies, 2016)
This pilot study looks at video games play of African students from a connected learning theory perspective. Interpreting the data through the lenses of connected learning theory principles, the findings reveal that learning takes place during video game play. Participants in the study show peer support, interest, shared purpose, academic orientation, and production centered principles from a connected learning perspective, describe a learning community. The paper concludes by connecting this principles to other skills used in video games literature to evidence learning.